A comparative evaluation of physical characteristics, bioactive compounds, and antioxidant capacity of Rhodomyrtus tomentosa berry by different drying methods - Dingjin, L.; Qiuxia, D.; Yipeng, G.; Nor Afizah, M.; Zhenhua, D.; Yingjian, L.; Jiao, D. (Rynnye Lyan Resources, 2024)
The Rhodomyrtus tomentosa berry (RTB) has attracted the attention of researchers for its medicinal and nutritional characteristics. However, there is limited research on the influence of different drying methods on RTB quality. The objective of this work was to evaluate the effect of vacuum microwave drying (VMD), heat pump drying (HPD), and sun drying (SD) on the quality characteristics, microstructure, and antioxidant capacity of RTB. Results indicated that compared with HPD and SD, VMD enhanced the quality of RTB and could complete the drying process in a shorter time (3.6 hrs). In addition, VMD was able to retain a higher level of bioactive compounds and antioxidant capacity with an improved rehydration ratio. The microscopic images showed that the VMD had an obvious porous structure, facilitating the water evaporation. This suggested that VMD is an efficient drying technology for producing high-quality dried products.